Stomach cancer complicated by perforation and acute bleeding - Pliuta , Iryna; Skuba, Volodymyr; Stets, Mykola; Trepet , Sergey; Ivanko , Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2023)
improvement and optimization of diagnosis and treatment of gastric cancer complications. 56 patients with gastric cancer complications were treated. The average age of the patients was 56 years. Of them, 13 (23.21%) were women amd 43 (76.79%) were men. During comprehensive diagnostic and therapeutic monitoring, it was found that 15 patients (26.79%) had gastrointestinal bleeding, 12 patients (21.43%) had gastric stenosis of various degrees, and the remaining 29 patients (51.79%) gastric cancer complicated by gastric perforation, of them, in 21 patients, perforation was accompanied by bleeding. Age and gender, preoperative diagnosis, localization of perforation, depth of gastric wall invasion, absence or presence of metastases in lymph nodes, type of operation, degree of lymphatic dissection, stage and complications were studied. The percentage of complications in the form of perforation among gastric cancer was 51.79%. The disease was more common in stage III/IV (70%). Operations performed: gastrectomy in 16 patients and suturing of perforation in 10 patients. Death related to surgery was observed in 4 patients. 10 subtotal gastrectomies and 6 total gastrectomies were performed. In 15 patients, clinically pronounced gastrointestinal bleeding was observed, which was manifested in the form of melena, hematemesis or in the form of melena and hematemesis simultaneously (2.5%). The mean age was 68 ± 12 (range 47–87). A complication in the form of gastric stenosis was detected in 12 patients (21.43%). During the study, subcompensated stenosis of the pyloric part of the stomach was detected in 5 patients, decompensated stenosis in the remaining patients. The choice of surgical intervention method was carried out individually, depending on the patient's condition, the degree of stenosis and the nature of pathomorphological changes, the state of the secretory and motor function of the stomach, the presence of accompanying pathology and the stage of gastric cancer. In this group of patients, there is 1 case of mortality, which was due to IV stage of gastric cancer and decompensated stenosis with pronounced disorders of water-electrolyte balance and acid-base balance.